Social Chemical Communication Determines Recovery From L1 Arrest via DAF-16 Activation - Mata-Cabana, Alejandro; Gómez-Delgado, Laura; Romero-Expósito, Francisco J.; Rodríguez-Palero, María J.; Artal-Sanz, Marta; Olmedo, María (Frontiers in Cell and Developmental Biology, 2020)
In a population, chemical communication determines the response of animals to changing environmental conditions, what leads to an enhanced resistance against stressors. In response to starvation, the nematode Caenorhabditis elegans arrest post-embryonic development as L1 larva right after hatching. As arrested L1 larvae, C. elegans become more resistant to diverse stresses, allowing them to survive for several weeks expecting to encounter more favorable conditions. L1 arrested larvae secrete unidentified soluble compounds that improve survival to starvation. This protection is proportional to larval population density. Thus, animals arrested at high densities display an enhanced resistance to starvation. Here we show that this chemical communication also influences recovery after prolonged periods in L1 arrest. Animals at high density recovered faster than animals at low density. We found that the density effect on survival depends on the final effector of the insulin signaling pathway, the transcription factor DAF-16. Moreover, DAF-16 activation was higher at high density, consistent with a lower expression of the insulin-like peptide DAF-28 in the neurons. The improved recovery of animals after arrest at high density depended on soluble compounds present in the media of arrested L1s. In a try to find the nature of these compounds, we investigated the disaccharide trehalose as putative signaling molecule, since its production is enhanced during L1 arrest and it is able to activate DAF-16. We detected the presence of secreted trehalose in the medium of arrested L1 larvae at a low concentration. The addition of this concentration of trehalose to animals arrested at low density was enough to rescue DAF-28 production and DAF-16 activation to the levels of animals arrested at high density. However, despite activating DAF-16, trehalose was not capable of reversing survival and recovery phenotypes, suggesting the participation of additional signaling molecules. We finally identified GUR-3 as a possible trehalose receptor in C. elegans. With all, here we describe a molecular mechanism underlying social communication that allows C. elegans to maintain arrested L1 larvae ready to quickly recover as soon as they encounter nutrient sources.